The Role of Tasybih Tamtsil in Enriching the Imagination of Arabic Literature - Muiz, Abdul; Hakim, Lutpiyah (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Tasybih tamtsil is a form of parable in Arabic rhetoric that has high expressive power. Its use in Arabic literature not only clarifies the meaning, but also enriches the reader's imagination by presenting a more concrete and vivid picture. This article aims to analyze the role of tasybih tamtsil in developing the aesthetics and imagination of classical and modern Arabic literature. With a qualitative-descriptive approach, this study reveals how tasybih tamtsil is used in literary works and how it affects readers' understanding and experience. The results of the study show that tasybih tamtsil not only increases the aesthetic power of Arabic literature, but also plays a role in strengthening the cultural and moral values that the author wants to convey.